Visa Regulation of Indonesian Migrant Worker Based on Immigration Control Act of Japan, 2018 (Medico Legal Update, 2021)
Japan as a developed country needs a lot of productive labor to fulfill its human resources needs. With therevised Immigration Act of 2018, Japan has opened up to accept many migrant workers, one of whom isIndonesian migrant worker who can fulfill these needs. The purpose of this research is to find out the form ofvisa regulation for Indonesian migrant workers in Japan based on the provisions of the Japan Immigration Act2018 and to know the efforts of the Indonesian Government can make in implementing the visa regulationsto facilitate Indonesian migrant workers who will work in Japan.